Pengembangan Ensiklopedia Digital Kearifan Lokal Kabupaten Kediri Untuk Meningkatkan Literasi Budaya Pada Siswa Sekolah Dasar - Nur Husna Afandi, Alia; Adhi Suciptaningsih, Oktaviani; Pristiani, Riska; Slamet (ELSE (Elementary School Education Journal) : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2025)
This research is based on the problem of learning resources that are not yet included in the independent curriculum and teachers' difficulties in finding relevant learning resources. The aim of this research is to produce teaching materials in the form of a digital encyclopedia of Kediri district local wisdom containing folklore, traditions, arts, typical clothing, tourism and typical food to develop valid, practical and effective fourth grade elementary school students' cultural literacy. This digital encyclopedia was developed in a structured manner involving analysis, planning, production and evaluation stages, guided by the Richey & Klein (2009) development model. The construction validation process resulted in a score of 90%, while material suitability validation was 89%. Both score results can be categorized as "very valid" for use. The process of analyzing the practicality of the extensive test stage obtained a teacher response score of 100% and a student response of 87%, so it can be said to be "very practical". The effectiveness analysis also shows that 96% of students at SDN Adan-Adan 2, totaling 17 students, succeeded in exceeding the Minimum Completeness Criteria (KKM) with an average class score of 86. The use of digital encyclopedias is expected to provide easier and faster access to information, facilitating student-centered learning and supporting increasing students' cultural literacy through knowledge of the local wisdom of Kediri Regency.